The impact of the medical emergency team on the resuscitation practice of critical care nurses. Issue 2 (6th January 2011) - Santiano, N; Young, L; Baramy, L S; Cabrera, R; May, E; Wegener, R; Butt, D; Parr, M; ,
Abstract : Background: Medical Emergency Teams (MET)/rapid response are replacing Cardiac Arrest teams in acute hospitals. There is a lack of knowledge about how Critical Care Nurses (CCNs), rostered on MET construct their responsibilities/roles. Objective: Assess MET nurse activities at different hospitals. Methods: The authors used visual ethnography; selecting Systemic Functional Grammar as our methodological framework. The Generic Systemic Potential was used to guide the coding of visual and inferential meaning of the activities of MET nurses. CCNs coded over 6 h of videoed MET calls, sampled across three hospitals, Sydney, Australia. Results: The first layer of coding contained 1042 discreet tasks. They were sorted into 15 Areas of Practice (AOPs) and then allocated to aspects of performance (psychomotor and cognitive). The AOPs 'Assisting with Procedure' through to 'Monitoring Vital Signs' reflect psychomotor skills which account for almost half (48%) of the AOPs at site 1 and three-quarters at sites 2 (70%) and 3 (78%). Eight generic responsibilities/roles were identified. 'Ongoing Assessment, ' 'Re-evaluating Risk' and 'Prioritising Interventions' were the most prominent. The patterns differed by hospital: 'Re-evaluating Risk' was prominent for sites 1 and 2 but less so for site 3. Conclusion: 'Ongoing Assessment' and 'Re-evaluating Risk' occupied almost half of the MET nurses time, whereas 'Establishing Patient Acuity, the key activity in CA teams, occupied only 4%. These findings provide evidence of the roles of CCNs in the MET and suggest that education and training of MET nurses should support these roles.